Culture contextualisation of mathematics instruction. A draw a scientist test (DAST) analysis - Makramalla, Mariam (AUC Knowledge Fountain, 2018)
This work intends to study preparatory school students’ perception of mathematics instruction within the local context of the Egyptian teaching and learning culture. The target is to unveil some insight about the power dynamics between teacher and student as well as amongst the students in the classroom. To address students’ perceptions of their own classroom mathematics pedagogy, the study adopts a sequential double filter integration method that is founded in literature. This method seeks to interpret preparatory school students’ drawings in response to a given prompt. The analysis unveils an apparent paradox in relation to the classroom power dynamics that is perceived by students. The results are then addressed and further synthesized with the help of a contextual understanding of the wider cultural framework. In addition to that, some principles of the social cognitive theory also serve as a platform for explaining the results. Future work needs to consider adopting the results of this study as part of a contextual comparative analysis; contrasting classroom power dynamics of different teaching and learning environments.